Sabotaging potential rivals - J. Atsu Amegashie; Marco Runkel (Center for Economic Studies and ifo Institute (CESifo), 2005)
This paper studies sabotage in a contest with non-identical players. Unlike previous papers, we consider sabotage in an elimination contest and allow contestants to sabotage a potential or future rival. It turns out that for a certain partition of players there is a pure-strategy equilibrium in which only the most able contestant engages in sabotage while less able contestants do not. The most able contestant may therefore prefer a situation where sabotage is allowed to one where sabotage is not allowed. For another partition of players, there is a unique equilibrium in which none of the players invests in sabotage.
Keywords: D74; D72; 330; all-pay auction; elimination contests; potential rival; sabotage; Wirtschaftskriminalität; Wettbewerb; Auktionstheorie; Spieltheorie